Social Policy against School Dropouts - Arief, Aulia Ramdhani (Journal Social Civilecial, 2023)
This article discusses social policies for school dropouts in Makassar. The number of children who have not yet taken formal education in Makassar is a problem that wants to be minimized with the awareness of education from all parties. This case of school dropouts is a very complicated case and is still difficult to solve until now. There are many factors behind school dropouts, including family, geography, social, economic and environmental factors. The purpose of this article is to find the factors that cause many children in Makassar to not receive equal education and to know the social policies for dropping out of school.